Insecticide resistance of Aedes aegypti in Indonesia: a systematic review - Sofiana, Liena; Rokhmayanti, Rokhmayanti; Martini, Martini; Wulandari, Dewi Ariyani (International Journal of Public Health Science (IJPHS), 2023)
In Indonesia, dengue hemorrhagic fever (DHF) continues to be an issue. Although there have been fewer dengue infections in the past three years, many areas of Indonesia remain dengue endemic. Insecticide use is one DHF prevention and control method that has been used for a long time. Long-term usage of insecticides can cause the vector, Aedes aegypti, to develop resistance. Insecticide resistance to Aedes aegypti in Indonesia was the focus of this study's analysis of the literature review. A systematic review using keywords based on population, interest and context (PICo) was employed in the study strategy. The databases used to find the publications were ScienceDirect, ProQuest, PubMed, Google Scholar, and Garuda from 2018 to 2022. Hence, 40 papers out of the 6,429 total articles were relevant and should be reviewed and analyzed. According to an analysis of the paper, it was discovered that Aedes aegypti mosquitoes are resistant to insecticides of the pyrethroid and organophosphate classes in various parts of Indonesia. However, it was discovered that several regions were both tolerant of and vulnerable to pyrethroids and organophosphates. If insecticides are to be utilized intolerant and vulnerable locations, monitoring and evaluation of their usage must be done, and a strategy of varying insecticide kinds and dosages and boosting community empowerment toward mosquito nest elimination behaviour must be implemented.